Drug-Induced Acute Dystonia After Sacubitril/Valsartan Combination - Prabhat Tewari; Shantanu Pande; Divya Arora (Annals of Internal Medicine: Clinical Cases)
Adverse drug reaction by definition can be an unpleasant response due to a drug use that can adversely affect a person and may call for either treatment or withdrawal of the medication. We found classical dystonia in a young girl who presented with reduced systolic left ventricular function, had cardiac surgery, and was prescribed sacubitril/valsartan combination for reversal of remodeling of the heart. The dystonia did not reoccur after stoppage of this combination. Although being an effective drug for heart failure with reduced ejection fraction, newer indications will need further assessment for the different dose regimen and adverse drug reactions.